Livelihoods-based Drought Response in Ethiopia: Impact Assessment of Livestock Feed Supplementation - Bekele, Gezu; Tsehay Abera (Tufts Archival Research Center, 2005)
Since the drought in some pastoralist areas of Ethiopia in 2005 to 2006, there has been increasing interest in the use of supplementary feeding for Livestock as part of an integrated drought response. Over time, and with more attention to the need for early response, NGOs are working to intervene more rapidly and improve modes of implementation. In terms of the livelihoods-based approaches promoted by the USAID Pastoralist Livelihoods Initiative, the livelihoods objectives of Livestock supplementary feeding are to protect the key assets of pastoralists and promote post-drought recovery. However, Livestock supplementary feeding is not universally accepted as an appropriate drought response intervention. For those actors following a conventional humanitarian approach of saving human lives, feed for Livestock might be regarded as a distraction from the core business of Food relief for people. Livestock feed supplementation also involves considerable costs, with some workers suggesting that these costs are somehow excessive or inappropriate.